Uma análise histórica sobre Os Elementos de Euclides. - DINIZ, Alex Santos Moura (2020)
In this work, we present a historical analysis of the work The Elements of Euclid, its structure, the method used, its definitions, axioms and propositions, which consist of relevant aspects for direct application in the classroom in the teaching of mathematics with an impact on basic education. The concern that justifies the motivation for the development of this work lies in the possibility of sharing the knowledge present in Os Elements de Euclides for high school and elementary students (final years). What we present in this work is the use of the knowledge present in Euclides' work in solving problems in the teaching of mathematics, especially with regard to book 1 and 2, in particular about the equivalence of areas, Pythagorean Theorem, square of flat figures and Greek geometric algebra. It is worth mentioning that the translation object of this work is the first complete translation into Portuguese made from the Greek text. We conclude that this work can be used in basic education, making the method simpler in solving problems, considering the available resources, as well as the reality of the student and the school community.